METHODOLOGICAL SKILLS WHEN USING THE WORKS OF PROFESSOR K.K. SARTBAEV - Sarybasheva K. (Vestnik Issyk-Kulʹskogo universiteta)
The issue of teaching Kyrgyz as a native language in comprehensive schools and teaching in it was again considered at the state level, a multi-year national program for the development of the Kyrgyz language as a native and state language was developed, and according to it, the state subject standard for teaching the Kyrgyz language in comprehensive schools, the curriculum also underwent significant changes and additions. The subject standard and the curriculum set the requirements for an innovative update of the goal and objectives of teaching the Kyrgyz language, content and means, and teaching technology. Such an update, first of all, concerns the content of teaching the Kyrgyz language, and the content was determined on the basis of specially established competencies. In particular, teaching the Kyrgyz language as a native language in secondary schools has become a legal requirement based on linguistic, speech and cultural competencies. There is a need to direct the rich methodological heritage of Professor K. K. Sartbaev to the formation of students' linguistic competence in teaching the Kyrgyz language, to supplement it, improve it and re-develop it in accordance with modern requirements.